P042 Targeting NF-Κb signalling in B cells: a potential new treatment modality for antibody mediated autoimmune diseases. (21st February 2018) - Van Hamburg, JP; Tuijnenburg, P; Helder, B; van Keep, L; Wesenhagen, K; Kucharzewka, P; Jansen, MH; Al-Soudi, A; Klarenbeek, PL; Olsson, H; de Vries, N; Kuijpers, T; et al.
Abstract : Introduction: The pivotal role of B cells in the pathogenesis autoimmune diseases such as ANCA-associated vasculitis (AAV) is well-established and further substantiated by beneficial therapeutic effects of rituximab (anti-CD20 B cell targeted therapy). However, this results in prolonged B cell depletion while long-lived plasma cells are not targeted. Thus there is a need for novel therapeutics targeting cells in the B-cell lineage in AAV. Novel targets might be encountered in the NF-κB signalling pathway, which acts downstream of various B cell surface receptors, including the B cell antigen receptor, CD40, BAFFR and TLRs, and is crucially involved in B cell responses. Objectives: To identify whether inhibition of NF-κB signalling by novel pharmacological inhibitors is effective in targeting B cell responses in general and more specifically blocks (auto)antibody production and plasmablast differentiation in B cells from AAV patients. Methods: PBMC and sorted B cells from AAV patients and healthy donors were cultured with T cell-dependent (anti-IgM +anti CD40+IL-21) and T cell-independent (CpG +IL-2) stimuli. NF-κB signalling was targeted in these cultures by small molecule inhibitors of NF-κB inducing kinase (NIK, non-canonical NF-κB signalling) and IKKβ (canonical NF-κB signalling). Downstream NF-κB signalling and nuclear NF-κB translocation was determined by Western blot and confocal imaging. Effects on B cell proliferation and differentiation were determined by CFSE dilution assays and flow cytometric analysis of B cell markers. (Auto)antibody production was measured by ELISA. Results: In B cells, targeting of NIK and IKKβ effectively inhibited non-canonical or canonical NF-κB signalling, respectively. In a B cell stimulation assay, NIK and IKKβ inhibition significantly reduced T cell-dependent (anti-IgM +anti CD40+IL-21) and T cell-independent (CpG +IL-2) B cell proliferation, plasmablast differentiation (CD27++/CD38+), and antibody production. The effects of NIK inhibition appeared to be B cell-specific as T cell proliferation was largely unaffected. Currently, studies are ongoing to investigate the effect of IKKβ inhibition on B cell responses and to explore the effects of targeting NF-κB signalling in AAV B cells. Conclusions: These data demonstrate that inhibition of NF-κB signalling in B cells results in the modulation of various B cell responses. Ongoing studies will indicate whether targeting of NF-κB signalling in B cells may be an effective novel treatment modality for AAV. Disclosure of interest: None declared